2008
DOI: 10.2220/biomedres.29.221
|View full text |Cite
|
Sign up to set email alerts
|

The effects of examination stress on salivary cortisol, immunoglobulin A, and chromogranin A in nursing students

Abstract: This study aimed to assess the effects of examination stress on salivary cortisol, immunoglobulin A (IgA), and chromogranin A (CgA) in nursing students. Saliva samples were collected from 15 healthy females before and immediately after the one-hour examination, and two hours after the examination. Salivary cortisol, IgA, and CgA concentrations were determined by enzyme-linked immunosorbent assay. Both IgA and CgA concentrations statistically increased immediately after the examination (P < 0.05) and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 17 publications
(19 reference statements)
3
63
1
6
Order By: Relevance
“…When the acute stress model was applied in our study, significant increases at 15 min were obtained in both salivary cortisol, as reported before (Geverink et al, 2002;Merlot et al, 2011), and CgA concentrations. The mean increase of CgA was of 31%, a value that is between the increases described in several human studies about acute stress for the effect of examination (26%; Takatsuji et al, 2008) and after venipuncture in children (49%; Lee et al, 2006). Moreover, in the study about social isolation stress using saliva sampling in cows was described as a mean increase of 50% after 30 min of social isolation (Ninomiya and Sato, 2011).…”
Section: Discussionsupporting
confidence: 51%
“…When the acute stress model was applied in our study, significant increases at 15 min were obtained in both salivary cortisol, as reported before (Geverink et al, 2002;Merlot et al, 2011), and CgA concentrations. The mean increase of CgA was of 31%, a value that is between the increases described in several human studies about acute stress for the effect of examination (26%; Takatsuji et al, 2008) and after venipuncture in children (49%; Lee et al, 2006). Moreover, in the study about social isolation stress using saliva sampling in cows was described as a mean increase of 50% after 30 min of social isolation (Ninomiya and Sato, 2011).…”
Section: Discussionsupporting
confidence: 51%
“…11 Salivary CgA, thus, has been proposed as a surrogate marker of sympathetic nervous system activity. 12 A series of studies has shown that compared with salivary cortisol, salivary CgA increases more rapidly and more sensitively to psychological stressors induced by activities such as public speaking, 12 word-processing and arithmetic tasks, 13,14 academic examinations, 15 and venipuncture in hospitalized children. 16 A recent finding from the author's laboratory further demonstrated that salivary CgA levels in the late-luteal phase significantly increased among women with severe premenstrual emotional symptoms, while salivary cortisol showed no menstrual-cyclic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that the concentrations of IgA and CgA presented a statistically significant increase immediately after the exam had finished and decreased after two hours. No significant differences were observed in the salivary cortisol concentration in the period covering 1 hour before the exam, immediately after it and 2 hours after it (26) . In a study that correlated stress and infectious diseases, a positive association was found between the common cold (61.7%) and herpes (21.3%).…”
Section: Discussionmentioning
confidence: 72%
“…Some (17,(19)(20)(22)(23)(25)(26) analysed the relationship between stress and physiological or psychological manifestations, and others (10,12,21,24,(27)(28) explored the general health state of the students involved in the researches.…”
Section: Resultsmentioning
confidence: 99%